2023
DOI: 10.1007/s00415-023-11706-1
|View full text |Cite
|
Sign up to set email alerts
|

Migraine: from pathophysiology to treatment

Abstract: Migraine is an extremely disabling, common neurological disorder characterized by a complex neurobiology, involving a series of central and peripheral nervous system areas and networks. A growing increase in the understanding of migraine pathophysiology in recent years has facilitated translation of that knowledge into novel treatments, which are currently becoming available to patients in many parts of the world and are substantially changing the clinical approach to the disease. In the first part of this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 225 publications
0
23
0
Order By: Relevance
“…CGRPs are also strongly associated with CM, with previous studies showing higher serum levels of CGRPs among patients with CM compared with patients with EM or no headache. 12,19 These findings have established the vital role of CGRPs in the pathophysiology of migraine. To achieve effective acute or preventative treatment, CGRP antagonists acting on CGRP receptors or ligands have been developed.…”
Section: Cgrps and Migrainementioning
confidence: 88%
See 2 more Smart Citations
“…CGRPs are also strongly associated with CM, with previous studies showing higher serum levels of CGRPs among patients with CM compared with patients with EM or no headache. 12,19 These findings have established the vital role of CGRPs in the pathophysiology of migraine. To achieve effective acute or preventative treatment, CGRP antagonists acting on CGRP receptors or ligands have been developed.…”
Section: Cgrps and Migrainementioning
confidence: 88%
“…13 In addition to this effect of the trigeminovascular system on brainstem regions, its activation further affects the hypothalamus, thalamus, and cortex, resulting in the unique features of migraine. 12 CM has different mechanisms and presentations comparing with those of EM. 14 Multiple studies have indicated a strong correlation between structural and functional changes in specific brain regions associated with pain sensitization and top-down pain modulation.…”
Section: Migrainementioning
confidence: 98%
See 1 more Smart Citation
“…Today, lasmiditan is the only ditan available. 103 The 5-HT1F receptor agonist lasmiditan is a centrally acting, selective, and high-affinity compound. It acts on the trigeminovascular system, inhibiting neurotransmitter release without causing vasoconstriction.…”
Section: Migraine Drugs and Their Synthesismentioning
confidence: 99%
“…Today, lasmiditan is the only ditan available . The 5-HT1F receptor agonist lasmiditan is a centrally acting, selective, and high-affinity compound.…”
Section: Migraine Drugs and Their Synthesismentioning
confidence: 99%